2014
DOI: 10.3171/2013.9.jns131337
|View full text |Cite
|
Sign up to set email alerts
|

Repeat digital subtraction angiography after a negative baseline assessment in nonperimesencephalic subarachnoid hemorrhage: a pooled data meta-analysis

Abstract: Object A repeat digital subtraction angiography (DSA) study of the cranial vasculature is routinely performed in patients with diffuse nonperimesencephalic subarachnoid hemorrhage (SAH) after negative baseline CT angiography (CTA) and DSA studies. However, DSA carries a low but substantial risk of neurological complications. Therefore, the authors evaluated the added value of repeat DSA in patients with initial angiographically negative diffuse nonperimesencephalic SAH. Methods A systematic review of the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 25 publications
1
31
0
1
Order By: Relevance
“…Even when DSA fails to demonstrate an aneurysm in the setting of spontaneous subarachnoid hemorrhage, delayed repeat imaging is indicated. One literature review identified 37 aneurysms out of 368 angiography-negative subarachnoid hemorrhage patients on delayed, repeat DSA from one to six weeks after their initial study [50]. The higher resolution of DSA also allows for better neck characterization to guide endovascular versus open surgical treatment and better visualization of associated branch vessels [30].…”
Section: Digital Subtraction Angiographymentioning
confidence: 99%
“…Even when DSA fails to demonstrate an aneurysm in the setting of spontaneous subarachnoid hemorrhage, delayed repeat imaging is indicated. One literature review identified 37 aneurysms out of 368 angiography-negative subarachnoid hemorrhage patients on delayed, repeat DSA from one to six weeks after their initial study [50]. The higher resolution of DSA also allows for better neck characterization to guide endovascular versus open surgical treatment and better visualization of associated branch vessels [30].…”
Section: Digital Subtraction Angiographymentioning
confidence: 99%
“…However, in up to 20% of patients with SAH, results of cerebral angiography, CT, and MRI are negative for aneurysms or other vascular malformations. 2,7,11 More recent data show an increasing number of cases of spontaneous SAH 18,24 as well as nonaneurysmal SAH (NASAH). 15,16 Long-term dipyridamole and warfarin use were associated with an increased risk for aneurysmal SAH (aSAH), whereas the data for low-dose acetylsalicylic acid (LDA) were inconsistent.…”
mentioning
confidence: 99%
“…Given the vasospasm period and the chance of a thrombosed aneurysm, it is reasonable to perform a repeat DSA at least 10–14 days after the ictus [20]. …”
Section: Methodsmentioning
confidence: 99%